A Study on Rent-to-Income Ratio in Residential Property Sector of Uyo, Akwa Ibom State, Nigeria - Akpan, Kufre; Raphael Nyeneime; Udosen, Victor (New Advances in Business, Management and Economics Vol. 6, 2025)
Some people who have financial capacity can afford to own a shelter, while some can only manage to rent it from those who can afford to own it. This study examined the rent-to-income ratio in the residential property market in Uyo, Akwa Ibom State, Nigeria. A sample of 427 residential property occupiers was reached based on interviews and questionnaires. Simple percentage, means, Analysis of Variance (ANOVA), and pairwise were used to analyse the data. The result revealed that 35.3% was the mean rent-to-income ratio in Uyo. Self-contained had the highest rent-to-income ratio of the occupiers as it took 40% of the income while tenement building had the lowest as it took 20% as the rent-to-income ratio. ANOVA showed a significant difference in the mean rent of occupiers based on the type of property as the mean rent was N303,898.10 while the lowest rent was N49,434.80 and the highest rent was N647,777.80 and no significant difference based on occupation. From the pairwise comparison of the mean rent by property type, the mean rent for the Maisonette was significantly higher than others, while the mean rent for the tenement was lesser than the mean rent of all other properties. The implication of this result is that rent default is a major risk in real estate investment and tenants who may maintain consistency in rent payment may neglect other basic needs. As the mean rent-to-income ratio is 35.3%, tenants should be sensitized to understand the recommended rent-to-income ratio of 30% to guide them in renting housing and the implications. Also, the government should provide a home ownership scheme where she can subsidise the sale of houses or land to encourage the citizens to have theirs. Public-Private-Partnership (PPP) schemes can also be encouraged to boost the housing supply, and this can help reduce the cost of housing.